2014
DOI: 10.1371/journal.pone.0092733
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 20–Year Organic and Inorganic Fertilization on Organic Carbon Accumulation and Microbial Community Structure of Aggregates in an Intensively Cultivated Sandy Loam Soil

Abstract: To evaluate the long–term effect of compost (CM) and inorganic fertilizer (NPK) application on microbial community structure and organic carbon (OC) accumulation at aggregate scale, soils from plots amended with CM, NPK and no fertilizer (control) for 20 years (1989–2009) were collected. Soil was separated into large macroaggregate (>2,000 μm), small macroaggregate (250–2,000 μm), microaggregate (53–250 μm), silt (2–53 μm) and clay fraction (<2 μm) by wet-sieving, and their OC concentration and phospholipid fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 62 publications
(80 reference statements)
7
33
0
3
Order By: Relevance
“…Assuming that the fungal population metabolizes the substrate more efficiently than bacteria (Otten et al, 2001;Keiblinger et al, 2010), we suppose that crushing decreased CUE by altering the soil microbial community structure. The decreased CUE after crushing was mainly pronounced in macroaggregates where the fungi presumably occur (Guggenberger et al, 1999;Zhang et al, 2014). Similarly, we also found that aggregate crushing did not affect the CUE (%0.45) in microaggregates in this study (Supplementary Table 1).…”
Section: Glucose Mineralization and Incorporation Into Labile Organicsupporting
confidence: 78%
See 1 more Smart Citation
“…Assuming that the fungal population metabolizes the substrate more efficiently than bacteria (Otten et al, 2001;Keiblinger et al, 2010), we suppose that crushing decreased CUE by altering the soil microbial community structure. The decreased CUE after crushing was mainly pronounced in macroaggregates where the fungi presumably occur (Guggenberger et al, 1999;Zhang et al, 2014). Similarly, we also found that aggregate crushing did not affect the CUE (%0.45) in microaggregates in this study (Supplementary Table 1).…”
Section: Glucose Mineralization and Incorporation Into Labile Organicsupporting
confidence: 78%
“…5). This result may be partly explained by the decreased role of fungi due to disruption of fungal mycelia by crushing, assuming that fungi are important PE drivers (Fontaine et al, 2011) and that fungi occur mainly in macroaggregates (Guggenberger et al, 1999;Zhang et al, 2014). In addition, the bacteria may switch from decomposing hardly utilizable substrates such as SOM to metabolizing the added glucose (preferential substrate utilization) (Paterson et al, 2007;Kuzyakov, 2010).…”
Section: Priming Effectmentioning
confidence: 99%
“…Over the past several years, many researchers have attempted to determine how to eliminate these obstacles through improving cultivation and management methods. Most research has focused on screening superior varieties to alleviate pests and disease, introducing grafting techniques to enhance plant resistance, applying organic fertilizer to improve soil quality, or selecting alternative rotations to balance soil nutrition [18][19][20]. However, the changes in soil quality due to continuous monoculture over several years or crops have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in bacterial communities may also be due to the effects of organic fertilizer on soil structure. Zhang et al (2014) showed that long-term applications of organic fertilizers accelerated the formation of soil aggregates, while simultaneously decreasing the oxygen diffusion coefficient, making microhabitats more suitable for anaerobes. The soil water content may also be driving shifts in the genetic structure and diversity of the bacterial communities under CM and EM.…”
Section: Discussionmentioning
confidence: 99%